A Review of Gelatine Formulations for Topical Skin Cancer Treatment (Asian Journal of Pharmaceutics (AJP), 2024)
Regarding both regional and widespread drugs, cancer of the skin, regardless of its manifestations, is the diseasewith the highest incidence rate in the world. Topical chemotherapy is an intriguing therapeutic approach due toits low cost and lack of invasiveness. Nonetheless, it is difficult to distribute antineoplastic drugs through the skindue to the numerous methodologies that have been utilized to ascertain the physicochemical features, includingsolubility, ionized molecular weight, and melting point, as well as the efficacy of the stratum corneum’s protectivebarrier, utilized to increase drug absorption, retention, and effectiveness. Its objectives are to determine the mostpopular methods for topical medication administration using gel-based medications for the treatment of skincancer. The preparation methods, the excipients employed, and the techniques for characterizing gels are brieflyexplained. Safety considerations are also emphasized.